2015
DOI: 10.5455/medarh.2015.69.6-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Anatomical Dominance of Coronary Circulation in Patients with Surgical Myocardial Revascularization

Abstract: Introduction:This study evaluated the frequency of domination of the coronary arteries types in patients treated by surgical myocardial revascularization. The aim of the study was to determine whether the left coronary circulation dominance is a prognostic factor for poorer outcome in patients undergoing coronary artery bypass surgery.Material and methods:A total sample consisted of 100 patients with coronary artery disease that were treated with coronary artery bypass grafting at the Clinic for Cardiac Surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Previous studies have demonstrated a close link between left coronary artery dominance and ACS or significant CAD [2325]. Left dominance has been identified as a predictor of non-fatal MI and all-cause mortality in patients with significant CAD [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a close link between left coronary artery dominance and ACS or significant CAD [2325]. Left dominance has been identified as a predictor of non-fatal MI and all-cause mortality in patients with significant CAD [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a co-dominant system, the supply of posterior IV septum is shared by both RCA and LCX[3]. Right dominant system is the more prevalent variant occurring in approximately 70% of people, followed by left dominant and co-dominant system[4]. …”
Section: Introductionmentioning
confidence: 99%
“…Left dominant system has been shown to be an independent risk factor of morbidity and mortality in patients undergoing both surgical and percutaneous revascularization, especially in patients with ST segment elevated myocardial infarction (STEMI)[4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…We called this technique, the SMR. Due to cardiac characteristics in pigs, the development of the model of SMR required a rigorous surgical learning curve to safely access the ascending aorta and achieve a selective retrograde perfusion of the great cardiac vein [8,9,[25][26][27]. The capacity of SMR to produce inotropic effects when associated with a simultaneous antegrade perfusion, was previously reported by us in a preliminary experience with OPCAB surgery [14].…”
Section: Discussionmentioning
confidence: 99%